Prenatal diagnosis of heterozygous deficiency of the second component of complement. - Sullivan, K E (1994)
Genetically determined C2 deficiency predisposes an individual to recurrent and invasive bacterial infections as well as a variety of rheumatic diseases. Most C2-deficient individuals carry the same 28-bp deletion in the sixth exon of the C2 gene. The present article reports the first prenatal analysis of a sibling of a C2-deficient patient; the sibling was found to be a heterozygous carrier of the 28-bp deletion of C2.